PTH-249 Contraceptive pill and b12: low yield from investigating low serum b12 in women taking the ocp. (22nd June 2015) - Clark, K; Chinnappan, L; Reilly, I; Probert, C
Abstract : Introduction: Vitamin B12 deficiency causes megaloblastic anaemia, cytopenias and neurological deficits and deficiency is usually a result of defective absorption, either through lack of intrinsic factor, gastric pathology or ileal pathology although dietary deficiency may occur. Serum B12 assays have low specificity and up to 50% of results below 200 ng/l appear erroneous. Patients could be committed to unnecessary B12 replacement therapy and symptoms may be wrongly ascribed to B12 deficiency as the real cause is overlooked. 70–90% of serum B12 is bound to holohaptocorrin, the remainder being bound to holotranscobalamin. These carrier proteins are affected by pregnancy and the oral contraceptive pill (OCP), resulting in a low B12 level in the absence of anaemia or macrocytosis. Our aim was to evaluate B12 testing in women of childbearing age by assessing firstly, concomitant use of the OCP and secondly where, the result was felt to indicate true deficiency, whether appropriate assessment was conducted. Method: Over a 12-month period, all women of childbearing age who were shown to have a low serum B12 level were eligible to be included. Repeat tests were excluded. We then reviewed Hb, MCV and ferritin and folate. Results of investigation were noted when performed including intrinsic factor, anti-GPC and TTG antibodies; endoscopy and small bowel imaging. Results: 180 case records were identified, complete data was available from 166. The two key groups are those with isolated low B12 and those with macrocytic anaemia. Of those with macrocytic anaemia, 4/10 had coexisting folate deficiency. Further assessment was inconsistent- 4/10 no further assessment, 2/10 further blood tests but no imaging and 4/10 had various tests. One patient was subsequently diagnosed with Crohn's disease. Those patients with an isolated low B12 result, 68 were taking the OCP. For the remainder there was no documentation to confirm or deny use. Of the 68 patients, 30/68 had undergone some form of further investigation. In 2/30 women taking the OCP with low B12 without anaemia, one had coeliac disease and one had anti-GC antibodies (but no IF antibodies). Conclusion: In those patients who are identified as having a low B12 level in the absence of anaemia or macrocytosis; use of the OCP should be considered. Investigation of low B12, when there is no anaemia and normocytosis, is unrewarding. Repeating the serum B12 level after stopping the OCP should confirm the cause and prevent unnecessary investigation. Where anaemia or macrocytosis is present a structured approach to further investigation should made to seek and identify significant pathology. This includes antibody testing, thyroid function and gastric + ileal assessment. Disclosure of interest: None Declared.